Sustainable development and equity in the Kenyan context - (:unkn) unknown (Kenya Law, 2015)
Equity, particularly intergenerational and intragenerational equity, is central to the concept of sustainable development. The rhetoric of equity has been incorporated in sustainable development instruments and is already part of customary international law. In Kenya the right to a clean and healthy environment which inter aliaincludes the right to have the environment protected for the benefit of present and future generations has been codified in the legal framework and the courts have had occasion to interpret this right in the Kenyan context. Kenya has however adopted an anthropocentric definition and approach to sustainable development, which places a lot of emphasis on human beings thus ignoring the ecological perspective in sustainable development. The authors argue that the environment has a right to be safeguarded and protected not necessarily for the benefit of human beings but for ecological reasons. This paper critically examines the principle of equity (intergenerational and intragenerational equity), and its centrality in the concept of sustainable development in Kenya. The intergenerational rights of future generations and of the environment are explored. Equally the intergenerational and intragenerational obligations of the present generations are assessed. The paper also discusses the extent to which equity has been incorporated into the Kenyan legal framework on environment and natural resources. It will also give Kenyan examples of natural resources that are rare and have been threatened by unsustainable use. With the enactment of the new Constitution[1], the Environmental Management and Coordination Act No. 8 of 1999 and the Environment and Land Court Act No. 11 of 2011 it is hoped that sustainable development which is informed by equity will be attained. Achieving sustainable development means that the carrying capacity of the ecosystems will be conserved and protected and that the future generations will have an opportunity to enjoy the fruits of sustainable development. In order to attain these goals the requisite long-term measures have to be taken in conserving environmental and natural resources. The authors argue that the policy, legal and institutional mechanisms put in place on how to fulfill our duties to the environment and future generations are not adequate as they are designed to handle problems of a short-term nature. The paper notes that most of the measures undertaken in Kenya in conserving environmental and natural resources are short-term and are not suitable in attaining intra and intergenerational equity. It also notes that most of the measures, policies and programmes geared towards attaining sustainable development are largely centered on human beings and thus do not adequately address ecological issues in the country.
Article published by Kenya Law
Equity, particularly intergenerational and intragenerational equity, is central to the concept of sustainable development. The rhetoric of equity has been incorporated in sustainable development instruments and is already part of customary international law. In Kenya the right to a clean and healthy environment which inter aliaincludes the right to have the environment protected for the benefit of present and future generations has been codified in the legal framework and the courts have had occasion to interpret this right in the Kenyan context. Kenya has however adopted an anthropocentric definition and approach to sustainable development, which places a lot of emphasis on human beings thus ignoring the ecological perspective in sustainable development. The authors argue that the environment has a right to be safeguarded and protected not necessarily for the benefit of human beings but for ecological reasons. This paper critically examines the principle of equity (intergenerational and intragenerational equity), and its centrality in the concept of sustainable development in Kenya. The intergenerational rights of future generations and of the environment are explored. Equally the intergenerational and intragenerational obligations of the present generations are assessed. The paper also discusses the extent to which equity has been incorporated into the Kenyan legal framework on environment and natural resources. It will also give Kenyan examples of natural resources that are rare and have been threatened by unsustainable use. With the enactment of the new Constitution[1], the Environmental Management and Coordination Act No. 8 of 1999 and the Environment and Land Court Act No. 11 of 2011 it is hoped that sustainable development which is informed by equity will be attained. Achieving sustainable development means that the carrying capacity of the ecosystems will be conserved and protected and that the future generations will have an opportunity to enjoy the fruits of sustainable development. In order to attain these goals the requisite long-term measures have to be taken in conserving environmental and natural resources. The authors argue that the policy, legal and institutional mechanisms put in place on how to fulfill our duties to the environment and future generations are not adequate as they are designed to handle problems of a short-term nature. The paper notes that most of the measures undertaken in Kenya in conserving environmental and natural resources are short-term and are not suitable in attaining intra and intergenerational equity. It also notes that most of the measures, policies and programmes geared towards attaining sustainable development are largely centered on human beings and thus do not adequately address ecological issues in the country.
Keywords: Sustainable Development; equity; Kenya